The Influence of School-Based Management on the Quality of Education in Private Vocational High Schools and Its Impact on employment Competitiveness - Sendy Yulfizar; Zulganef Zulganef (Research Collaboration Community (RCC), 2023)
Empirical studies and literature studies on school-based management have indeed been carried out by many researchers and academics before. However, most have not discussed the implementation of SBM specifically in terms of curriculum and learning processes. Based on this, this study intends to deepen knowledge about SBM, especially regarding influence on the quality of education in private vocational high schools and its impact on employment competitiveness. According to the findings of several previous research, the impact of implementing SBM has demonstrated positive results in several aspects of the school, including student attendance, academic achievement, and school management specifically in terms of curriculum and learning processes. as well as the effect of SBM on employment competitiveness show that there are six elements that help students become more competitive, including strong school-community ties, curriculum that adheres to industry standards, qualified teachers, modern facilities, and infrastructure that meet industry standards, availability of adequate funding for the SMK program, and motivated and enthusiastic students. Additionally, there are five factors that prevent students from becoming more competitive at the vocational high school level. These factors include teachers' subpar abilities, a lack of government and industry collaboration, subpar facilities and infrastructure, minimal and restricted sources of funding for schools, and graduates who lack the skills and motivation to find employment. so that it can be concluded that SBM greatly influences the quality of educators and employment competitiveness.